Determinants of Myopia Severity Based on Behavior and Genetic Factors: Determinanan Derajat Myopia Berdasarkan Perilaku dan Faktor Genetik - Rapael Ginting; Buenita S; Ashila Zahrani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Myopia is a leading global vision disorder affecting quality of life and projected to impact over half the world’s population by 2050. Specific Background: Among university students, behavioral factors such as prolonged near work and gadget use, alongside genetic predisposition, are recognized contributors, yet findings remain inconsistent, particularly in public health student populations. Knowledge Gap: Limited studies have specifically identified dominant determinants of myopia severity in public health students, a group expected to champion health promotion. Aims: This study aimed to determine the behavioral and genetic factors most strongly associated with myopia severity among Public Health students at Universitas Prima Indonesia. Results: Using a cross-sectional analytic design with 74 diagnosed myopic students, multivariate logistic regression revealed significant associations with reading distance <30 cm, gadget use >3 hours/day, and family history, with genetic factors showing the highest odds ratio (AOR = 8.567, p = 0.002). Gender was not significant. Novelty: The study uniquely combines primary and secondary data, integrates multivariate analysis, and aligns findings with the Ottawa Charter for Health Promotion and SDG 3. Implications: Results support campus-based preventive strategies, including visual hygiene education, gadget use reduction, and early screening for genetically at-risk students.Highlight : Genetic factors are the most dominant determinant of the degree of myopia. Hours of gadget use and close reading increase the risk of myopia. Health promotion on campus is important for preventing the progression of myopia. Keywords : Myopia, Derajat Myopia, Mahasiswa Kesehatan Masyarakat, Penggunaan Gadget, Faktor Genetik